2(3/5x+3)-(2/3x-1)=2

Simple and best practice solution for 2(3/5x+3)-(2/3x-1)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3/5x+3)-(2/3x-1)=2 equation:



2(3/5x+3)-(2/3x-1)=2
We move all terms to the left:
2(3/5x+3)-(2/3x-1)-(2)=0
Domain of the equation: 5x+3)!=0
x∈R
Domain of the equation: 3x-1)!=0
x∈R
We multiply parentheses
6x-(2/3x-1)+6-2=0
We get rid of parentheses
6x-2/3x+1+6-2=0
We multiply all the terms by the denominator
6x*3x+1*3x+6*3x-2*3x-2=0
Wy multiply elements
18x^2+3x+18x-6x-2=0
We add all the numbers together, and all the variables
18x^2+15x-2=0
a = 18; b = 15; c = -2;
Δ = b2-4ac
Δ = 152-4·18·(-2)
Δ = 369
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{369}=\sqrt{9*41}=\sqrt{9}*\sqrt{41}=3\sqrt{41}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(15)-3\sqrt{41}}{2*18}=\frac{-15-3\sqrt{41}}{36} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(15)+3\sqrt{41}}{2*18}=\frac{-15+3\sqrt{41}}{36} $

See similar equations:

| 2(3/5x+3)-(2/3x-1)=5 | | 2(3/5x+3)-(2/3x-1)=8/15x+5 | | (3x+2)°=41 | | 2(3/5x+3)-(2/3x-1)=8/15x+3 | | 2(3/5x+3)-(2/3x-1)=8/15x+7 | | 1220000/X=62/38,x= | | 15+x=23-2 | | x=180(14-2) | | (4x+2)(x-8)=0 | | -4(2+2x)=-16 | | 2(v-6)=-8 | | (2x+10)(2x-7)=0 | | X-6=4x-12 | | (2x-9)(2x-8)=0 | | 4(-)2(v-6)=-8 | | 2(3x+9)+4(2x+6)=4(x+10)+7 | | 2(a-8.5)-2.6=3.1+7.4 | | (2x+9)(2x-8)=0 | | 70=3x+6x+7 | | 1x+1=3.75 | | 400+1x=6x | | 72=32b^2 | | 4x3−30x+8=34 | | 2(x-5-7=2 | | 13^x+2=5 | | -3x-9+6x=-9 | | 2(2x)+(12-2)=3x+13 | | .025x+50=x | | 2x+4=10-4^x | | -4t^2+19t-211=0 | | (1+0.1x)^6=1 | | 2×y=76 |

Equations solver categories